IMPLEMENTASI METODE MULTI SOURCE FEEDBACK (MSF) DALAM PENILAIAN PERILAKU PROFESIONAL MAHASISWA KEBIDANAN PADA PRAKTIK KLINIK KEBIDANAN FISIOLOGIS - Rusfita Retna; Reni Sumanti (Unit Penelitian dan Pengabdian Masyarakat, Politeknik Banjarnegara, 2018)
Health worker competence are Ethics, Moral, Medikolegal and Professionalism and Patient Safety. Professionalism is one of the important factors that a midwife must possess. Evaluation of learning outcomes becomes an important point for DIII program students in shaping professional behavior. Multi Source Feedback (MSF) is one of the valid and reliable assessment methods in assessing professional behavior of midwifery students. The objective of the study was to identify the implementation of Multi Source Feedback (MSF) in midwifery clinical assessment to evaluate professional behavior of midwifery students. This research was conducted in Program of Midwifery Polytechnic Banjarnegara with student population of third semester. The number of sample is 29 students, 4 academic supervisors, and 29 peer review (peers). Respondents were selected based on total sampling. This research was conducted for 6 months. The results showed that the average value of professional behavior is 3 which means the students are in good category. The number of students wich scored below the average was only 10 respondents (35%). This shows that the learning process in Program D III Midwifery Polytechnic Banjarnegara is good. MSF can be implemented as an assessment of methods in a clinical setting because it is more objective.